2009
DOI: 10.1126/science.1162819
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamonds in the Younger Dryas Boundary Sediment Layer

Abstract: We report abundant nanodiamonds in sediments dating to 12.9 +/- 0.1 thousand calendar years before the present at multiple locations across North America. Selected area electron diffraction patterns reveal two diamond allotropes in this boundary layer but not above or below that interval. Cubic diamonds form under high temperature-pressure regimes, and n-diamonds also require extraordinary conditions, well outside the range of Earth's typical surficial processes but common to cosmic impacts. N-diamond concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
152
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(161 citation statements)
references
References 7 publications
(4 reference statements)
7
152
1
1
Order By: Relevance
“…At Bull Creek, YDB nanodiamonds were initially reported at a concentration of 102 p.p.b. [3]. Later, Bement et al [8] reported a three order-of-magnitude larger 190 p.p.m.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…At Bull Creek, YDB nanodiamonds were initially reported at a concentration of 102 p.p.b. [3]. Later, Bement et al [8] reported a three order-of-magnitude larger 190 p.p.m.…”
mentioning
confidence: 99%
“…Controversial 'i-carbon' is also reported at the YDB of many sites [6,7]. While neither are diamond polytypes, impact proponents describe them as nanodiamonds [3][4][5][6][7][8]. In YDB sediments, 'n-diamonds' are usually reported at higher abundances than diamond [6,7].…”
mentioning
confidence: 99%
See 3 more Smart Citations